Big data, data mining and machine learning : value creation for business leaders and practitioners - Dean, Jared, 1978- (Hoboken, New Jersey : John Wiley and Sons, Inc., 2014)
"An expert guide to high performance computing architectures and how they relate to analytics and data miningWith the exponential growth of data comes an ever-increasing need to process and analyze so-called Big Data. High Performance Data Mining and Big Data Analytics provides a comprehensive view of the recent trend toward high performance computing architectures and its natural connection to analytics and data mining. You'll find coverage of topics including: big data, high performance computing for analytics, massively parallel processing (MPP) databases, in-memory analytics, implementation of machine learning algorithms for big data platforms, text analytics, analytics environments, the analytics lifecycle, general applications, as well as a variety of cases. Offers coverage of business analytics, predictive modeling, and fact-based management Includes case studies featuring multinational companies Explores recent trends in high performance computing architectures relating to data mining Filled with case studies, High Performance Data Mining and Big Data Analytics provides a thorough grounding for optimally putting data mining and big data analytics to work for your organization"--
Hardware -- Distributed systems -- Analytical tools -- Predictive modeling -- Common predictive modeling techniques -- Segmentation -- Incremental response modeling -- Time series date mining -- Recommendation systems -- Text analytics -- Case study of a large U.S.-based financial services company -- Case study of a major health care provider -- Case study of a technology manufacturer -- Case study of online brand management -- Case study of mobile application recommendations -- Case study of a high-tech product manufacturer -- Looking to the future.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Management -- Data processing; Data mining; Big data; Database management; Information technology -- Management; COMPUTERS -- Database Management -- Data Mining; Big data; Data mining; Database management; Information technology -- Management; Management -- Data processing; Data Mining; Massendaten; Maschinelles Lernen; Managementinformationssystem; Electronic books; Electronic books